Daucus carota L. as a source of natural pigment and its effect on zootechnical parameters in Cobb 500 broiler chickens: Producción y Salud Animal - Jácome-Gómez, Janeth Rocío (2023)
This study evaluated the effect of carrot flour (CF; Daucus carota L.) as a partial substitute for the basal diet of Cobb 500 broiler chicken on skin pigmentation, production parameters and profitability. A total of 64 chickens were separated according to sex and assigned to four diets, with four replicates of two birds each. The control groups were fed a standard diet, and the experimental groups were fed the same conventional diet with replacement levels of 10, 15, and 20% CF. No significant differences were observed in feed consumption, weight gain or feed conversion ratio. However, diets with carrot flour improved feed intake, promoted weight gain and optimized feed efficiency with 10% in males and 15% in females. No mortality was recorded in the experimental groups. The intensity of pigmentation in the chickens’ skin increased as the level of substitution increased, while sex influenced color expression. Diets with CF improved profitability especially in males. In conclusion, the replacement of the basal diet with CF in the diet of Cobb 500 broilers had positive effects on the evaluated parameters, therefore, it can be used as an alternative source of natural pigment in the production of yellow-skinned broilers.